Conceptualizing Professional Identity Formation in Medicine - Sarraf-Yazdi, Shiva; Goh, Suzanne; Krishna, Lalit (Academic medicine, 2024)
Professional Identity Formation (PIF) in medicine is the gradual transformation that occurs in the process of becoming a doctor, as professional values, beliefs, behaviors, relationships, roles, and responsibilities become integrated into an aggregate of existing identities. 1 Conceptually, this process may be considered as a trajectory of self-perceived identities that transpires between an individual's existing identity and an evolving, aspirational identity toward which the individual may strive. 2 This process is individualized, yet contextual, psychosocially grounded, and subject to lifelong deconstruction and reconstruction depending on how the person experiences, and thus responds to, events. 2. Faced with key transitions, conflicts, or crises, a medical student or physician may experience dissonance between their personal values and beliefs and their professional roles and expectations.1 If left unsupported (see light blue lines in graph below), this can challenge their sense of belonging or meaning, lower self-esteem or self-efficacy, or breed distress, burnout, or attrition. When recognized and supported (see dark blue line below), defining experiences can enhance tolerance for ambiguity, enable meaning-making, foster socialization into communities of learning or practice, and deepen enculturation and commitment to the profession. 2. PIF is implicitly a fundamental goal of medical education, necessitating institutional support along the medical education continuum. 1-3.